2020
DOI: 10.18051/jbiomedkes.2021.v4.70-78
|View full text |Cite
|
Sign up to set email alerts
|

Hubungan antara beban kerja, besaran upah, dan stres kerja pada karyawan PT. HBSP

Abstract: LATAR BELAKANG Perkembangan dunia bisnis yang dinamis tentu berpengaruh terhadap tuntutan produktivitas kerja karyawan. Dalam menjalankan tugas mereka tidak jarang para karyawan mengalami stres kerja yang bisa diakibatkan oleh berbagai faktor antara lain beban kerja dan besaran upah kerja. Tujuan dari penelitian ini adalah untuk mengetahui hubungan antara beban kerja, besaran upah dengan stres kerja pada karyawan PT. HBSP.   METODE Studi cross-sectional pada 95 karyawan PT. HBSP. Data s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
1
0
0
Order By: Relevance
“…The variable of workload did not demonstrate a significant relationship with the level of work distress during the COVID-19 pandemic (p-value = 0.179). This finding aligns with research by Sarifa [55], which similarly concluded that there was no significant relationship between physical workload and the incidence of work stress in employees. Despite being categorized for improvement, the workload was manageable and effectively handled by employees within the company.…”
Section: Analysis Of the Relationship Between Work Factors (Content O...supporting
confidence: 91%
“…The variable of workload did not demonstrate a significant relationship with the level of work distress during the COVID-19 pandemic (p-value = 0.179). This finding aligns with research by Sarifa [55], which similarly concluded that there was no significant relationship between physical workload and the incidence of work stress in employees. Despite being categorized for improvement, the workload was manageable and effectively handled by employees within the company.…”
Section: Analysis Of the Relationship Between Work Factors (Content O...supporting
confidence: 91%